2019
DOI: 10.1093/nar/gkz064
|View full text |Cite
|
Sign up to set email alerts
|

Cationic porphyrins with large side arm substituents as resonance light scattering ratiometric probes for specific recognition of nucleic acid G-quadruplexes

Abstract: Specific G-quadruplex-probing is crucial for both biological sciences and biosensing applications. Most reported probes are focused on fluorescent or colorimetric recognition of G-quadruplexes. Herein, for the first time, we reported a new specific G-quadruplex-probing technique—resonance light scattering (RLS)-based ratiometric recognition. To achieve the RLS probing of G-quadruplexes in the important physiological pH range of 7.4-6.0, four water soluble cationic porphyrin derivatives, including an unreported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…With the addition of l -CatG4 or d -CatG4, the fluorescence at 714 nm greatly increased, accompanied by the decrease in fluorescence at 657 nm. Since neither single- nor double-stranded DNA has been reported to affect the UV–vis absorption and fluorescence signal of TMPipEOPP, the above-observed optical responses were G-quadruplex-specific and were consistent with previous reports. These results further demonstrated that both l -CatG4 and d -CatG4 could fold into G-quadruplex structures to bind with porphyrin.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…With the addition of l -CatG4 or d -CatG4, the fluorescence at 714 nm greatly increased, accompanied by the decrease in fluorescence at 657 nm. Since neither single- nor double-stranded DNA has been reported to affect the UV–vis absorption and fluorescence signal of TMPipEOPP, the above-observed optical responses were G-quadruplex-specific and were consistent with previous reports. These results further demonstrated that both l -CatG4 and d -CatG4 could fold into G-quadruplex structures to bind with porphyrin.…”
Section: Resultssupporting
confidence: 87%
“…The above-mentioned experiments demonstrated that the l -DNA-based G-quadruplex could also bind with Hemin. In our previous works, we have designed a series of highly specific G-quadruplex ligands by introducing bulky side arm substituents into cationic porphyrin derivatives, and found that they could give pronounced optical responses to G-quadruplexes. Here, we used one of our cationic porphyrin compounds (TMPipEOPP) as a G-quadruplex probe and compared the binding interactions of this porphyrin with l -CatG4 and d -CatG4.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PS2.M could be more promising as a detection probes for Pb 2+ in environmental samples, because they caused a suitable absorption signal in CD spectroscopy. The limits of permissible concentration of Pb 2+ in surface water are as follows: 50 ppb for drinking water supply 41 ; 15 ppb for drinking water 42 ; 50-100 ppb for permissible effluent water 43 ; and 200-500 ppm industrial wastewater 36 . In Fig.…”
Section: Analysis Of Pb 2+ Spiked Into Wastewater Samples In Order Tmentioning
confidence: 99%
“…Amongst the aromatic macrocycles, porphyrins, such as the cationic H2TMPyP and analogs appear as the most widely tested telomerase inhibitors [32,33,[53][54][55]. Structural attributes such as the presence of an extended heteroaromatic moiety that can interact on the G-quartet surface of a G-quadruplex by π−π stacking, and flexible cationic charged terminal side chains are pointed as essential features for effective ligand binding to a quadruplex and optimal inhibition of telomerase activity [9].…”
Section: Interactive G-quadruplex Ligands and Gq Recognition Modesmentioning
confidence: 99%
“…Other im structural characteristics are the presence of bulky substituents to prevent inter with double-stranded DNA and good solubility in aqueous media. In gener matic/planar molecules such as porphyrins and analogs, especially if positively c Amongst the aromatic macrocycles, porphyrins, such as the cationic H 2 TMPyP and analogs appear as the most widely tested telomerase inhibitors [32,33,[53][54][55].…”
Section: Interactive G-quadruplex Ligands and Gq Recognition Modesmentioning
confidence: 99%